Improving care – improving access: the use of electronic decision support with AIDS patients in South Africa. (26th May 2009) - Mitchell, Marc; Lesh, Neal; Cranmer, Hilarie; Fraser, Hamish; Haivas, Irina; Wolf, Kate
The shortage of physicians has severely limited the expansion of AIDS treatment programs in Africa. This paper presents a novel approach to scaling up treatment utilising counsellors with specially developed clinical algorithms on a hand-held computer to screen patients and maintain patient records in settings where doctors are limited. We screened AIDS patients in two clinics in South Africa to determine whether they could safely continue their current treatment regimen or required consultation with a physician. Following these validation trials, we will scale up this program and include linkage of these algorithms with patient records stored on the device.